Ownership Structure, Voting, and Risk - Dhillon, Amrita; Rossetto, Silvia (Review of Financial Studies, 2015)
We analyze the determinants of a firm's ownership structure when decisions over risk are taken by majority vote of risk-averse shareholders. We show that when a fraction of small, diversified shareholders abstains from voting, mid-sized blockholders may emerge to mitigate the conflict of interests between one large shareholder, who prefers less risky investments, and these small, non-voting shareholders. The paper offers a novel explanation for the puzzling observation that many firms have multiple blockholders. The paper develops numerous empirical implications, for example on the link between ownership structure and risk choices and on the relative size of blocks.